Chapter 12 – In conclusion: how to manage fisheries? - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED • What is the real state of fisheries around the world? • What experiences have we on the assessment and management of different fish populations? • When should we invest, or refrain from investing or intervening, in the fishing industry?